Development and use of new sensitive molecular tools for diagnosis and detection of Melampsora rusts on cultivated poplar. Issue 1 (8th October 2012) - Husson, C.; Ioos, R.; Andrieux, A.; Frey, P.; Hantula, J.
Mmd